Ophelia a novel - Klein, Lisa (Bloomsbury, 2008)
In a story based on Shakespeare's Hamlet, Ophelia tells of her life in the court at Elsinore, her love for Prince Hamlet, and her escape from the violence in Denmark
"Extra Extra read all about it, bonus materials inside"--P. [4] of cover
Keywords: Revenge / Fiction; Murder / Fiction; Princes / Fiction